Carbon savings in the UK demand side response programmes. (1st December 2015) - Lau, E.T.; Yang, Q.; Stokes, L.; Taylor, G.A.; Forbes, A.B.; Clarkson, P.; Wright, P.S.; Livina, V.N.
Highlights: We model carbon emissions and savings in DSR programmes with Smart interventions. We consider STOR, Triad, Fast Reserve programmes, and Irish Smart Metering project. We model reserve energy generation by conventional OCGT and CCGT power plants. DSR interventions are diesel generators, hydro-pump storage, demand reduction and shift. Carbon savings are difference between business-as-usual and intervention emissions. Abstract: We quantify carbon (CO2 ) savings in the demand side response (DSR) programmes. We consider Short Term Operating Reserve (STOR), Triad, Fast Reserve and Smart Meter roll-out, with various types of smart interventions involved (using diesel generators, hydro-pumped generation and use of tariffs). We model CO2 emissions in each of the DSR programmes with appropriate configurations and assumptions used in the energy industry. This enables us to compare carbon emissions between the business-as-usual (BAU) solutions and the smart intervention applied, thus deriving the carbon savings. Whether such DSR produces positive CO2 savings or not depends on the used technologies, as well as the scale of the interventions, which we illustrate in examples.